2021
DOI: 10.1128/aem.01169-21
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Ditropolonyl Sulfide, an Antibacterial Compound Produced by Burkholderia cepacia Complex Strain R-12632

Abstract: Burkholderia cepacia complex strain R-12632 produces ditropolonyl sulfide, an unusual sulfur-containing tropone, via a yet unknown biosynthetic pathway. Ditropolonyl sulfide purified from a culture of strain R-12632 inhibits the growth of various Gram-positive and Gram-negative multidrug resistant bacteria, with minimum inhibitory concentration (MIC) values as low as 16 μg/ml. In the present study we used a transposon mutagenesis approach combined with metabolite analyses to identify the genetic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Tropone natural products such as tropodithietic acid [TDA ( 10 )], roseobacticides [e.g., roseobacticide A ( 11 )], ditropolonyl sulfide ( 12 ), and tropolone ( 13 ) are known for their antimicrobial, antifungal, and anticancer activities as well as for their role as signaling molecules (e.g., in quorum sensing). , All of these compounds contain a seven-membered aromatic carbon ring system, decorated with a keto function contributing to the aromaticity of these molecules . Isotope labeling experiments combined with gene knockout studies have shown that bacterial tropone natural products are predominantly derived from phenylacetic acid ( 14 ) and that sulfur amino acid and glutathione metabolism are crucial for sulfur incorporation. , In the past decade, the investigation of 14 catabolism in bacterial species led to the serendipitous discovery of the shunt product 2-hydroxycyclohepta-1,4,6-triene-1-formyl-CoA ( 15 ) that because of its structural characteristics was proposed as the universal precursor for tropone natural products in bacteria …”
Section: Flavoenzyme-dependent Tropone Biosynthesis In Proteobacteriamentioning
confidence: 99%
“…Tropone natural products such as tropodithietic acid [TDA ( 10 )], roseobacticides [e.g., roseobacticide A ( 11 )], ditropolonyl sulfide ( 12 ), and tropolone ( 13 ) are known for their antimicrobial, antifungal, and anticancer activities as well as for their role as signaling molecules (e.g., in quorum sensing). , All of these compounds contain a seven-membered aromatic carbon ring system, decorated with a keto function contributing to the aromaticity of these molecules . Isotope labeling experiments combined with gene knockout studies have shown that bacterial tropone natural products are predominantly derived from phenylacetic acid ( 14 ) and that sulfur amino acid and glutathione metabolism are crucial for sulfur incorporation. , In the past decade, the investigation of 14 catabolism in bacterial species led to the serendipitous discovery of the shunt product 2-hydroxycyclohepta-1,4,6-triene-1-formyl-CoA ( 15 ) that because of its structural characteristics was proposed as the universal precursor for tropone natural products in bacteria …”
Section: Flavoenzyme-dependent Tropone Biosynthesis In Proteobacteriamentioning
confidence: 99%